Morphological Characteristics of Os Subfibulare Related to Failure of Conservative Treatment of Chronic Lateral Ankle Instability. (February 2020) - Lee, Doo Jae; Shin, Hyuck Soo; Lee, Jae Hee; Kyung, Min Gyu; Lee, Kyoung Min; Lee, Dong Yeon
Background: The os subfibulare is usually asymptomatic and found incidentally on radiographs. However, sometimes it may cause subfibular pain and may be associated with chronic lateral ankle instability (CLAI). We hypothesized that os subfibulare could interrupt the talofibular space causing impingement, resulting in chronic pain and functional instability around the lateral malleolus. The purposes of this study were to analyze morphologic characteristics of os subfibulare, and to evaluate the clinical significance of the os subfibulare in patients with CLAI. Methods: Between November 2011 and April 2015, 70 patients who had both computed tomography (CT) and magnetic resonance imaging (MRI) among 252 patients who visited our hospital with the symptom of lateral ankle instability were included in this study. The location of the ossicle was classified into 3 zones in reference to the attachment site of the lateral ankle ligaments. The impingement was classified into 2 groups according to the presence of talofibular encroachment. Digital radiographs were used to measure the ossicle width and shape determined by the length and width on an magnetic resonance (MR) image. Results: The most common shape of ossicles was oval, and the most common location of ossicles was at the anterior talofibular ligament (ATFL) attachment site. Sixty-one percent of patients showed talofibular impingement on coronal MR images. In 48 cases, the dimension of fibula plus os subfibulare was larger than that of the contralateral normal fibula. The larger size and talofibular impingement of the ossicle were associated with greater need for operative treatment in patients with ankle instability. Conclusion: The morphologic analysis of the os subfibulare revealed that there might be impingement of the talofibular space by the ossicle in some patients. We suggest that morphologic characteristics of the os subfibulare should be considered when selecting treatment options in patients with CLAI and os subfibulare. Level of Evidence: Level III, retrospective comparative series.